About hop cones for a golden brew - Jurášek, Michal; Rybka, Adolf; Opletal, Lubomír; Drašar, Pavel (Chemické listy, 2022)
As a component of drinks, food, cosmetics, and spice, hops yields a plethora of biologically active compounds. This plant, which was valued by gods and kings through the history, may serve as a basis for pharmaceutical ex-ploitation: not only as a healthy folk medicine but also in asearch for the effective sedative, estrogenic, antimicro-bial, antidiabetic, and cancerostatic compounds.
Keywords: Oils, Volatile; Plants, Medicinal; Humulus; léčivé rostliny; oleje prchavé; Beer; Medicine, Traditional; pivo; tradiční lékařství